Implementation of Augmented Reality Technology in the Design of the Kaswari Elok 87 Ship as a Tourism Vessel in the Sea Area of West Papua - Andani, Tri Rejeki; Diptya Widayaka, Parama (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2025)
The lack of interactive visualization media in presenting tourism transportation information in West Papua has become an obstacle in attracting interest and understanding among potential users. This study implements augmented reality (AR) technology to present the interior and exterior design of the MV Kaswari Elok 87 ship in an interactive and realistic manner. AR technology enables detailed visualization of the ship without the need for a physical model, thereby facilitating the design presentation process. The application was developed using Unity 3D and tested on two Android devices. The results show that the system can display the ship model stably with optimal performance at a distance of 20–190 cm and a 360° viewing angle, achieving an average frame rate of 33 FPS. Keywords: augmented reality, image processing, marker detection, rendering